Positioning Strategies: A Review of the Role of Commercial Teams - Prieto-Flórez, Javier (EFIM Ediciones, 2022)
The current competitive landscape in organizations, characterized by highly demanding consumers with respect to products and services that meet their needs, has generated challenges and challenges increasingly changing and dynamic, leading organizations to strengthen their commercial teams, adapting to these new demands, however, in many cases these organizations do not have a broad overview of the strategies that allow them to meet the changing needs of their consumers in a timely manner. It is for this reason that a systematic review of the literature is proposed to elucidate some strategies that influence the positioning of organizations. In that order of ideas, the present proposal analyzes 33 scientific articles published from 2016 to March 2022 that have as their central theme strategies for commercial teams in organizations and their relationship with organizational performance. Key findings suggest that having a body of theory and practice backed by empirical evidence can help organizations address current constraints and challenges, thereby increasing market positioning. The findings propose an added value to be incorporated into strategies suggesting future lines of research, addressing empirical analysis.